KAJIAN ISLAM TERHADAP PROBLEM POLITIK UANG DALAM PILKADA DI INDONESIA - Abdul Wahid (An-natiq Jurnal Kajian Islam Interdisipliner, 2021)
It's not only the citizen (constituent) who determines the image of mayor election (Pilkada) but also anybody who influences the citizen in order to gain the support from people has big influence through the image of democracy. One of political bad habits and law deviations which blot the image of mayor election (Pilkada) is money politics. It's the time for each people to not mortgage the democracy through money politics, since money politics can only make the future of country becomes even worse as a non-ethics country. In the Islamic doctrine, money politics can be categorized as bribing practice or a forbidden activity